Моделювання калієвих іонних каналів з урахуванням іонно-конформаційної взаємодії в рамках синергетичного підходу - Вайнреб, Г.Є.; Єсилевський, С.О. (Біополімери і клітина, 2001)
Проаналізовано одну з можливих математичних моделей, що описує калієвий іонний канал з рухливою структурою в рамках розвиненого раніше синергетичного підходу. Показано можливість виникнення за рахунок іонно-конформаційної взаємодії мультистабільних режимів функціонування каналу. Підтверджено правильність описання процесів активації-деактивації каналу на основі запропонованого підходу. Проаналізовано поведінку кінетичних параметрів каналу при змінах зовнішньої концентрації калію. Дано якісне пояснення природи виникнення концентраційних залежностей та досліджено питання щодо можливості появи немонотонностей у цих залежностях. Пояснено деякі особливості вольт-амперної характеристики каналу. Здійснено порівняння отриманих результатів з наявними експериментальними даними Проанализирована одна из возможных математических моделей, описывающая калиевый ионный канал с подвижной структурой в рамках развитого ранее синергетического подхода Показана возможность возникновения за счет ионно-конформационного взаимодействия мультистабильных режимов функционирования канала. Подтверждена правильность описания процессов активации–деактивации канала на основании использованного подхода. Проанализировано поведение кинетических параметров канала при изменении внешней концентрации калия. Дано качественное объяснение природы возникновения концентрационных зависимостей и исследован вопрос относительно возможности появления немонотонностей у этих зависимостей. Объяснены некоторые особенности вольт-амперной характеристики канала. Осуществлено сравнение полученных результатов с существующими экспериментальными данными. In this article one of the possible mathematical models of potassium ion channel with mobile structure is discussed. The basic conception of the model was developed earlier. This conception postulates the conformational changes in the channel molecule caused by the strong local electric field of the permeating ions inside the channel. Charged groups, moved by this field, slowly relax to the initial position after the ion passing and affect the energy profile for subsequent permeating ions. The system shows the self-organization, which leads to the appearance of the discrete open and closed conductivity states. This conception is applied to the potassium channel The model correctly describes the activation-deactivation processes. A special attention is paid to the concentration dependencies of the channel's kinetic constants and states occupancy probabilities, which are qualitatively explained. It is shown that Hodgkin-Huxley parameters α and β are [Kout]-dependent and the channel conductance in the closed state is much more sensitive to [Kout] than in the open one. The existence of the non-monotonous concentration dependencies, obtained in some experiments, is investigated. It is shown that the model proposed gives essentially monotonous dependencies. Some unusual features of volt-ampere characteristics are explained. The results obtained are compared with the experimental data earlier reported.